Áreas Naturales Protegidas en el ámbito metropolitano de las provincias de Lima y Callao (Perú) - Giacomotti, José (2025)
Natural Protected Areas of Peru conserve representative samples of biodiversity and contribute to the sustainable development of the country. The present research is a review article that aimed to document the information obtained on the main characteristics and the diversity of wild flora and fauna of three Natural Protected Areas (NPAs) that are located within the metropolitan area of the provinces of Lima and Callao, on the central coast of Peru. The Natural Protected Areas of Metro- politan Lima (capital of Peru) were studied as the Regional Conservation Area “Sistema de Lomas de Lima” (coastal hills ecosystem) and the Wildlife Refuge “Los Pantanos de Villa” (coastal wetland ecosystem), while the Constitutional Province of Callao studied the Regional Conservation Area “Humedales de Ventanilla” (coastal wetland ecosystem). For this purpose, a review of bibliogra- phic material was carried out in different specialized search engines and digital libraries on their general characteristics and their flora and wildlife. The results indicated that these three Natural Protected Areas have an important diversity of wild flora and fauna and provide environmental benefits to the cities of Lima and Callao, being necessary their conservation through the care and protection of their ecosystems of hills and wetlands, the promotion of tourism, the development of scientific research and environmental education.